Are preschool Kosovar children anxious on the edge? Validating the Preschool Anxiety Scale - Samire BLLACA BALAJ; Merita SHALA; Mimoza SHAHINI; Pranvera JETISHI ÇOLLAKU (Journal of Health and Social Sciences, 2024)
Introduction: Our current study aimed to test the reliability, validity, and factorial structure of PAS for Kosovar preschool children. Additionally, we sought to explore the anxiety levels in these children and the demographic variables influencing their anxiety. Methods: We designed the study as a non-experimental and cross-sectional. Parents of 676 preschool children (48.8 % girls) aged 3 to 7 years (M = 5.12; SD = 1.21) responded via an online questionnaire. The confirmatory factor analysis was conducted using IBM SPSS Amos, Version 25.0. The means and standard deviations, reliabilities (Cronbach’s α and mean inter-item correlations), scale intercorrelations for the focal test (PAS), and McDonald’s Omega for internal consistency were computed. Through correlation, t-test, ANOVA and MANOVA we investigated age, gender, parents living place and birth order effects on the PAS Results: Factor analysis validated the original five-factor model after removing two items, suggesting a shorter 26-item version for Kosovar preschoolers. The scale demonstrated a good internal consistency (α = .88/ωt =.875). For the subscales there were no differences in values from Cronbach’s α and McDonald’s Omega ωt: obsessive‐compulsive subscale (.71), social phobia (.78), physical injury fears (.72), and separation anxiety (.79) were in fair range, while it was in poor range for the generalized anxiety (0.55). 16.3% of children were found to have significant anxiety symptoms. Older children, female children and children who live in villages scored significantly higher on some subscales as well as on the PAS total scores. Discussion: Our study presented the first evidence to establish the validity and reliability of the PAS for Kosovar preschool children. Its good psychometric properties provide initial security for the assessment of a wide range of anxiety symptoms in preschool children in Kosovo.